Dominant factors affecting self-efficacy of emergency department nurse in implementing resusitation - Ahsan, Ahsan; Tualeka, Abdul Rohim; Rahmawati, Pudji; S Russeng, Syamsiar; Susilowati, Indri H; jalaludin, Juliaa (Opción, 2020)
The purpose of this research is to analyze the most dominant factors that influence the self-efficacy of emergency room nurses in carrying out resuscitation in cardiac arrest patients at RSUD Dr. R. Koesma Tuban via observational analysis with a cross-sectional study approach. As a result, the resulting coefficient of significance was mastery experience (p = 0.043) and verbal persuasion (p = 0.039) which is smaller than 0.05, showing a meaningful relationship. In conclusion, mastery experience was the dominant factor influencing the self-efficacy of emergency room nurses in carrying out resuscitation in cardiac arrest patients in the emergency room.